KEMAMPUAN MENGGUNAKAN KATA KERJA â€œRENWEIâ€ DAN â€œYIWEIâ€ OLEH MAHASISWA/I STBA-PIA MEDAN SEMESTER IV TAHUN AKADEMIK 2021/2022 - Hualangi, Anthony; Permatasari, Ayu (Linguistik : Jurnal Bahasa dan Sastra, 2023)
This research aims to determine the ability of STBA-PIA Medan Semester IV 2021/2022 Academic Year students to use the verbs "renwei" and "yiwei" and describe the factors that influence this ability. This research uses an integrative research design, where quantitative descriptive research methods are combined with qualitative research methods. The sampling technique used the Cluster Random Sampling technique, namely 33 STBA-PIA Medan students Semester IV 2021/2022 Academic Year and Research Subjects using the Purposive Sampling technique, namely, 3 students with the highest scores and 3 students with the lowest scores. The results of data analysis show that the ability of fourth semester students is relatively high with an average score of 80. The score that appears most often (mode) is 85, the middle score (median) is 85 and the standard deviation is 13. In addition, there are 9 people (27.27%) were classified as having very high ability, 13 people (39.39%) were classified as having high ability, 8 people (24.24%) were classified as having moderate ability and there were 3 people (9.1%) who are classified as having very low abilities. The factors that influence the abilities of STBA-PIA students are motivation factors, formal presentation factors, first language factors, and environmental factors (formal and informal).